2020
DOI: 10.1021/acsaem.0c00789
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Overall Water Splitting Activity of Templateless Structured Graphitic Nanoparticles Obtained from Cyclodextrins

Abstract: Pyrolysis of α-, β-, and γ-cyclodextrins at 900 °C under Ar forms porous 3D graphitic carbon nanoparticles with remarkable crystallinity, in which the pore dimensions range from 0.74 to 1.1 nm in the ultra/micropore range as determined by N2, Ar, and CO2 adsorption. These materials behave as semiconductors with the potential energy of the conduction and valence bands being remarkably dependent in as much as 0.57 eV on the dimensions of the micropores. The photogeneration of electrons and holes was confirmed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 36 publications
1
18
0
Order By: Relevance
“…The valence band energy maximum was estimated from XPS by determining the minimum energy to observe the appearance of electrons, resulting in a potential of 1.364 V versus normal hydrogen electrode (NHE) after correction by the work function of the instrument (see the Supporting Information for a detailed description of the calculations). [ 42 ] From this value, the conduction band energy minimum was deduced by adding the optical bandgap. Figure illustrates the alignment of the valence and conduction band energy values with respect to the potential required for H 2 and O 2 generation from H 2 O at pH 0.…”
Section: Resultsmentioning
confidence: 99%
“…The valence band energy maximum was estimated from XPS by determining the minimum energy to observe the appearance of electrons, resulting in a potential of 1.364 V versus normal hydrogen electrode (NHE) after correction by the work function of the instrument (see the Supporting Information for a detailed description of the calculations). [ 42 ] From this value, the conduction band energy minimum was deduced by adding the optical bandgap. Figure illustrates the alignment of the valence and conduction band energy values with respect to the potential required for H 2 and O 2 generation from H 2 O at pH 0.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the relative photocatalytic activity follows the order mp-(P)­C α > mp-(P)­C β > mp-(P)­C γ . This is in line with the previous observation of the positive influence of a small pore size on the (photo)­catalytic activity. , This relative photocatalytic activity order was also measured at various P contents, showing the positive influence of H 2 O confinement and small pore size on the photocatalytic reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Under optimal conditions, the mp-(P)C exhibits a much enhanced photocatalytic activity for overall water splitting under simulated sunlight illumination as compared to the parent mp-C material, reaching values that are among the highest ever reported for a C-based photocatalyst in the absence of any metal for overall water splitting. As for the parent mp-C materials, an influence of pore size on the photocatalytic activity has been observed for mp-(P)­C, with the most active material being the one with the smallest pore diameter.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…[1][2][3] In this regard, we recently reported the uniqueness of cyclodextrin pyrolysis, since these organic capsules form particulate graphitic carbon residues with (ultra) micropores of uniform subnanometric dimensions. 4,5 Cyclodextrins are cyclic molecular oligomers of 1,4-glucopyranose with a rigid geometry of truncated cones of 0.79 nm height. [6][7][8][9] The diameter of the cone is a function of the number of glucose units ranging for external larger diameters from 1.37 to 1.69 nm for aand g-cyclodextrins, respectively.…”
Section: Introductionmentioning
confidence: 99%